Do native predators benefit from non‐native prey?. (25th August 2015) - Pintor, Lauren M.; Byers, James E.; Anderson, Marti
Abstract Despite knowledge on invasive species' predatory effects, we know little of their influence as prey. Non‐native prey should have a neutral to positive effect on native predators by supplementing the prey base. However, if non‐native prey displace native prey, then an invader's net influence should depend on both its abundance and value relative to native prey. We conducted a meta‐analysis to quantify the effect of non‐native prey on native predator populations. Relative to native prey, non‐native prey similarly or negatively affect native predators, but only when studies employed a substitutive design that examined the effects of each prey species in isolation from other prey. When native predators had access to non‐native and native prey simultaneously, predator abundance increased significantly relative to pre‐invasion abundance. Although non‐native prey may have a lower per capita value than native prey, they seem to benefit native predators by serving as a supplemental prey resource.